TrbK, a small cytoplasmic membrane lipoprotein, functions in entry exclusion of the IncP alpha plasmid RP4. - Haase, J (1996)
TrbK is the only plasmid-encoded gene product involved in entry exclusion of the broad-host-range plasmid RP4. The corresponding gene, trbK, coding for a protein of 69 amino acid residues maps in the Tra2 region within the mating pair formation genes. TrbK carries a lipid moiety at the N-terminal cysteine of the mature 47-residue polypeptide. The mutant protein TrbKC23G cannot be modified or proteolytically processed but still acts in entry exclusion with reduced efficiency. An 8-amino-acid truncation at the C terminus of TrbK results in a complete loss of the entry exclusion activity but still allows the protein to be processed. TrbK localizes predominately to the cytoplasmic membrane. Its function depends on presence in the recipient cell but not in the donor cell. TrbK excludes plasmids of homologous systems of the P complex; it is inert towards the IncI system. The likely target for TrbK action is the mating pair formation system, because DNA or any of the components of the relaxosome were excluded as possible targets.